Cover and Table of Content - Journal of Mathematics Education, AlphaMath: (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2024)
FOREWORDAssalamu’alaikum Wr. Wb. Praise the presence of Allah SWT for all the overflow of His Rahmat so that we can publish the journal AlphaMath volume ten number one. The creation of the journal AlphaMath aims to develop a writing culture for educators, both teachers and lecturers. Apart from that, the AlphaMath journal seeks to accommodate all aspirations, ideas, and potential in the field of education, particularly mathematical education. The production of this journal aligns with the goal and mission of Muhammadiyah University's Department of Mathematics Education in Purwokerto. Its concept and mission are excellent regarding educational vocations and mathematical competencies.This journal's content is mostly concerned with mathematical education. This is done to encourage educators to innovate in their teaching and share their ideas with others. Hopefully, this journal will be assessed continuously to improve its quality. AlphaMath's current version includes articles on learning methods, mathematics skills, emotional talents, literacy, and technology use. All articles in this edition (11 research articles) include 40 authors from 3 countries of origin (Japan; China; Indonesia)Hopefully, this AlphaMath journal can provide benefits for readers and educational actors.Wassalamu’alaikum Wr. Wb.